Rethinking “Logistics Platforms”: the case of the North Adriatic Gateway - Dean, Marco; Fabbro, Sandro (TeMA - Journal of Land Use, Mobility and Environment, 2011)
The objective of this paper is to explore more realistic and sustainable territorial and logistics strategies (see Fabbro, Mesolella, 2010) in order to reconnect the Italian infrastructural system to the wider network of European corridors. Until this moment, the logistics and strategic national plans have not been selective concerning the identification, along the TEN-T Corridors, of a few ports and freight villages which are able to become effective European gateways within the Italian territory and attract private investments. Moreover, these planning instruments, instead of basing their strategies on the most concrete corridors have preferred to conceive their policies on entirely “imaginary” ones. This is, for instance, the case of the Logistics Platform in the Nord-East area of Italy. This Platform has been organized around the uncertain Corridor V, rather than the more concrete (but not yet recognized in the European maps) Adriatic-Baltic corridor. As a consequence, in this Region, several existing national infrastructures appear, at the moment, largely underused: a freight village of considerable size and European standards such as the Interporto Alpe Adria in Cervignano del Friuli, and an international double railway such as the “Pontebbana” that links the North-East area of Italy with Austria, through the Alpine pass of Tarvisio, and which is already the southern segment of the Adriatic-Baltic corridor. On the other hand, these infrastructures might play a significant role in light of the positive estimates about the new trends of maritime trades, which would realize a renewed centrality to the Mediterranean Sea (Drewry Shipping Consultants, 2010), and important development programs regarding the Adriatic ports, involving both public (Venice, Rijeka) and private (Monfalcone-Triest, Koper) stakeholders. The aim of these projects is to increase the competitive capacity of the North Adriatic port system and establish a more effective connection between it and the central and eastern parts of Europe, through the Baltic-Adriatic Corridor, so as to constitute the so-called North Adriatic Gateway. Similarly it would be possible to use the same strategies even for the the Nord-West territories which could depict the second important Italian gateway, the so-called North Tyrrhenian Gateway (based on the Two Seas Corridor 24 Genova-Rotterdam). The paper concludes its argumentations supporting the necessity of putting more emphasis on the Corridor 1, the Two Seas Corridor 24 and the Adriatic-Baltic corridor instead of the Corridor V. In fact only these North-South Corridors, linking Italy to the most productive European regions, could allow to produce economic benefits in a shorter term, while in this possible scenario, the Corridor V (hierarchically subordinate to the other axis) would connect the two Italian gateways each other and these ones to the second-level national infrastructure, in order to avoid the marginalisation of entire regional areas from the major trade and economic networks.